Endophytic fungi from wild banana (Musa acuminata Colla) works against anthracnose disease caused by Colletotrichum musae - Nuangmek W. (2014)
Screening of endophytic fungi which antagonize Colletotrichum musae, the cause of anthracnose disease, was carried out. The in vitro screening was studied by dual culture method. The inhibition due to fast competitive growth of Cordana sp. (KPP-3) and the antibiotic producing endophyte; Nodulisporium sp., reached a high percentage (90% C. musae inhibition). Spore germination assay showed 91% C. musae germination, while only 0.63 and 1.88% germinated in the conidial suspension of Cordana sp. and Nodulisporium sp., respectively. There was a significant difference between the Disease Severity Index (DSI) of banana fruits treated with Cordana sp. and those treated with Nodulisporium sp. The results presented in this research highlight the possibility of using endophytic fungi as biological control agents for anthracnose disease of banana. © 2008 Academic Journals Inc.